Can a Trial of Motivational Lifestyle Counseling be Effective for Controlling Childhood Obesity and the Associated Cardiometabolic Risk Factors? - Roya Kelishadi; Mohammad Malekahmadi; Mahin Hashemipour; Mehrnaz Soghrati; Mojgan Soghrati; Parisa Mirmoghtadaee; Shohreh Ghatrehsamani; Parinaz Poursafa; Noushin Khavarian (Elsevier, 2012)
This study was conducted to assess the effectiveness of a simple office-based program for encouraging healthy lifestyle on controlling childhood obesity and associated cardiometabolic risk factors. Methods: This non-randomized 24-week lifestyle modification trial was conducted among 457 obese children and adolescents, aged 2-18 years, who had at least one cardiometabolic risk factor in addition to obesity. This trial included three components of exercise, diet education and behavior modification, with all recommendations provided by a pediatrician, two general physicians and a nurse. Instead of strict inhibitory recommendations, healthier lifestyle was encouraged. Results: Overall 448 (98.04%) of enrolled children completed the trial with a mean age of 9.6 ± 2.9 years. After the trial, the mean of anthropometric measures and cardiometabolic risk factors decreased significantly, the mean high-density lipoprotein cholesterol (HDL-C) increased significantly, and the prevalence of the metabolic syndrome decreased from 20.8% to 1.8%. Triglycerides, LDL-C, diastolic blood pressure and WC had the highest decrease in all age groups, with the most prominent changes in the 14-18-year age group. By each -1SD decline in BMI and WC, risk factors had significant improvement. Conclusion: Motivational office-based counseling can be effective in treatment of childhood obesity and its associated cardio-metabolic risk factors. Such approach can be implemented in the primary health care system; and can be of special concern in low- and middle-income countries with limited human and financial resources. We suggest that expanding the roles of non-physician clinicians such as nurse practitioners can help to increase the amount of time available for such services.